Front cover: Micro‐proteomics with iterative data analysis: Proteome analysis in C. elegans at the single worm level. Issue 3 (February 2016) - Bensaddek, Dalila; Narayan, Vikram; Nicolas, Armel; Brenes Murillo, Alejandro; Gartner, Anton; Kenyon, Cynthia J.; Lamond, Angus I.
Abstract : DOI:10.1002/pmic.201500264 Using Caenorhabditis elegans as a model system, this study describes the development of a streamlined and reproducible 'micro‐proteomics' workflow, allowing global proteomics analysis from single worms. This picture combines an image of a C. elegans worm of the same type used in the study (a slightly edited mosaic picture acquired in the Gartner lab) with peptide sequences identified in the dataset, an example MS2 spectrum, and in the background a heatmap from the article. For details see the article by Dalila Bensaddek et al. on page 381.